Implementation of the Mamdani Fuzzy Method for Gourami Aquaculture Water Quality Control Using Pump Systems - Senthelee Vannessa Lai; Alicia Maharani; Naufa Hilmatuzzahra; Luthfi Alviani; Michael Lim Sony Wijaya (Batrisya Education, 2026)
Water quality stability is a critical factor in the cultivation of gourami fish (Osphronemus gouramy), as this species is highly sensitive to environmental changes. This study aims to implement the Mamdani fuzzy logic method in a pump-based water quality control system. The system is designed to analyze three primary parameters: temperature, ammonia concentration, and pH. Data acquired from sensors are processed by an ESP32 microcontroller through the stages of fuzzification, rule evaluation, implication, aggregation, and centroid-based defuzzification. A total of 48 fuzzy rules are formulated to adaptively determine the pump operating duration, allowing the system to adjust according to actual pond conditions. The experimental results show that at a temperature of 28.7 °C, an ammonia concentration of 0.28 ppm, and a pH value of 8.15—consistent with the simulation—the system produces a defuzzification output of 60 seconds, representing the pump operating duration. These findings confirm that the proposed system can generate flexible control decisions by considering the combined influence of multiple environmental parameters rather than relying on fixed threshold values. The implementation of the Mamdani fuzzy logic method improves system responsiveness in maintaining water quality stability in gourami aquaculture.